Neuroeconomic Measures of Social Decision-Making Across the Lifespan - Zhu, Lusha; Walsh, Daniel; Hsu, Ming (Frontiers in Neuroscience, 2012)
Social and decision-making deficits are often the first symptoms of a striking number of neurodegenerative disorders associated with aging. These includes not only disorders that directly impact dopamine and basal ganglia, such as Parkinson’s disorder, but also degeneration in which multiple neural pathways are affected over the course of normal aging. The impact of such deficits can be dramatic, as in cases of financial fraud, which disproportionately affect the elderly. Unlike memory and motor impairments, however, which are readily recognized as symptoms of more serious underlying neurological conditions, social and decision-making deficits often do not elicit comparable concern in the elderly. Furthermore, few behavioral measures exist to quantify these deficits, due in part to our limited knowledge of the core cognitive components or their neurobiological substrates. Here we probe age-related differences in decision-making using a game theory paradigm previously shown to dissociate contributions of basal ganglia and prefrontal regions to behavior. Combined with computational modeling, we provide evidence that behavioral deficits in elderly participants is driven primarily by an over-reliance in trial-and-error reinforcement learning that does not take into account the strategic context, which may underlie elderly’s susceptibility to fraud.